Language Choice in Bilingual School in SMP Hikmatul Fadhillah Medan - Eliza, Nur; Deliana; Lubis, Roma Ayuni A (Talenta Publisher, 2022)
This study analyzes language choice, the cause and effects of language choice by students in SMP Hikmatul Fadhillah Medan. The research method used is qualitative method by giving questionnaire to get the results of the analysis. Language choice that used in SMP Hikmatul Fadhillah Medan is English. The data identified according to the theory of Dell Hymes, SPEAKING: setting, participant, end, key, instrumentalities and norm of interaction is the cause that can influence the language choice for every person. Based on the data analysis by Ralph Fasold Theory: The effects of language choice iscaused by the occurrence of language, social, and cultural contacts. The effects of language choice is 58,6% for bilingual/multilingual, 20,7% for social contacts (communication & interaction), 13,8% for mix language and 6,9% for cultural contact (habit) . From the data 17 students choose bilingual/multilingual as the answer, 6 students choose social contact as the answer, 4 students choose mix language as the answer and 2 students choose cultural contact as the answer. The result taken from the 29 answered of the students in one class in grade VIII SMP Hikmatul Fadhillah Medan.